SISTEM INFORMASI PENGOLAHAN DATA PELANGGAN PADA CV. INDOPRINT BANDA ACEH - Zulkarnain Zulkarnain (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2020)
Customer Data Collection Information System is one of the data processing activities in the CV. Indoprint Banda Aceh, to get information about customers becomes more directed and easily obtained. In this study, the authors only discuss customer problems and customer data management mechanisms in the CV. Indoprint Banda Aceh and design a Customer Data Collection Information System using Microsoft Visual BASIC.NET. The purpose of writing is to understand customer problems and data management on the CV. Indoprint Banda Aceh and create a support application on the Customer Data Collection System using Microsoft Visual BASIC.NET. Data collection needed in writing this report was obtained by two methods, namely literature study relating to the literature of library books and other scientific works, field studies by carrying out interviews and direct observation of objects related to this research. The Customer Data Collection Information System is carried out by an administrative staff member to record and input customer data. From the results of this study, it can be concluded that the Customer Data Collection Information System at CV. Indoprint Banda Aceh has followed the procedure and used a computer with the Microsoft Visual BASIC.NET programming language.